"People in Hell Want Slurpees": The Redefinition of the Zombie Genre through the Salvific Portrayal of Family on AMC's The Walking Dead. Issue 1 (2nd January 2016) - Ambrosius, Joshua D.; Valenzano III, Joseph M.
Abstract : AMC's popular, post-apocalyptic show The Walking Dead follows a clan of survivors as they endure the zombie apocalypse while struggling to maintain their humanity. The characters pursue temporal salvation through four social institutions: family, government, religion, and science/medicine, identified by a preliminary soak. Through content analysis of dialogueic, visual, and nonverbal references to these institutions across seasons 1–3 ( N = 35), we find that each respective season proposed, and then rejected to some extent, the redemptive roles of science, religion, and the state—mirroring actual contemporary distrust. Simultaneously, through persistent, underlying storylines, the show reveals a traditional understanding of the centrality of familial relationships to maintaining a liberal society's survival—which we argue redefines the zombie genre away from its leftist roots.